A new multi-motor drive system based on two-stage direct power converter - Kumar, Dinesh (2011)
The two-stage AC to AC direct power converter is an alternative matrix converter topology, which offers the benefits of sinusoidal input currents and output voltages, bidirectional power flow and controllable input power factor. The absence of any energy storage devices, such as electrolytic capacitors, has increased the potential lifetime of the converter. In this research work, a new multi-motor drive system based on a two-stage direct power converter has been proposed, with two motors connected on the same shaft. A vector control scheme is proposed where each motor has an independent current control loop, but shares a single speed control loop. The two-motor on the same shaft solution has applications in aerospace to increase the availability of the system. The two-stage direct power converter therefore offers the possibility of a cost effective multi-motor drive system. The feasibility and performance of the proposed multi-motor drive system is demonstrated through simulation results and validated with experimental results from a laboratory prototype.